Technopolis Best Practices for Science and Technology Cities - Oh, Deog-Seong; Phillips, Fred (Springer London : Imprint: Springer, 2014)
Six years of UNESCO-World Technopolis Association workshops, held at various world cities and attended by government officials and scholars from nearly all the world's countries, have resulted in a uniquely complete collection of reports on science park and science city projects in most of those countries. These reports, of which a selected few form chapters in this book, allow readers to compare knowledge-based development strategies, practices, and successes across countries. The chapters illustrate varying levels of cooperation across government, industry, and academic sectors in the respective projects - and the reasons and philosophies underlying this variation - and resulting differences in practices and results.